2015
DOI: 10.5539/gjhs.v8n2p64
|View full text |Cite
|
Sign up to set email alerts
|

Effective Dose of Radon 222 Bottled Water in Different Age Groups Humans: Bandar Abbas City, Iran

Abstract: Radon 222 is a natural radioactive element with a half-life of 3.8 days. It is odorless and colorless as well as water-soluble. Consuming waters which contain high concentration of 222Rn would increase the effective dose received by different age groups. It would also be followed by an increased prevalence of cancer. In this research, 72 samples of the most commonly used bottled water in Bandar Abbas were collected in 3 consecutive months, May, June and July of 2013. Concentration 222Rn of was measured by rado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(30 reference statements)
1
8
0
2
Order By: Relevance
“…On the other end, in spite of having greater radio-sensitivity due to juvenile tissues, the portion of annual effective dose received by infants and children are on lower side as their quota of water consumption is very less compared to that of adults. The present findings were in agreement with the findings of Fakhri et al (2016) in that annually received effective dose by male and female adults were higher than children and infants due to more water consumption. Moreover, significant transformations in the effective dose received by different age groups of infants, children, teens, adult men, and women can be attributed to variation in their amount of water consumption rate and utilization of same dose conversion coefficient for all age groups.…”
Section: Estimation Of Annual Effective Dosesupporting
confidence: 93%
See 3 more Smart Citations
“…On the other end, in spite of having greater radio-sensitivity due to juvenile tissues, the portion of annual effective dose received by infants and children are on lower side as their quota of water consumption is very less compared to that of adults. The present findings were in agreement with the findings of Fakhri et al (2016) in that annually received effective dose by male and female adults were higher than children and infants due to more water consumption. Moreover, significant transformations in the effective dose received by different age groups of infants, children, teens, adult men, and women can be attributed to variation in their amount of water consumption rate and utilization of same dose conversion coefficient for all age groups.…”
Section: Estimation Of Annual Effective Dosesupporting
confidence: 93%
“…Moreover, significant transformations in the effective dose received by different age groups of infants, children, teens, adult men, and women can be attributed to variation in their amount of water consumption rate and utilization of same dose conversion coefficient for all age groups. Despite less per-capita drinking water consumption in infants, the study by Fakhri et al (2016) reported higher effective dose for infants over children, probably due to usage of bigger conversion coefficient for infants over children and adults. Overall, it can be stated from the present study that amount of water consumption by lactating women and male adults over other age groups has resulted in higher annual effective dose in them compared to that for pregnant women, adult females, teenagers, children, and infants.…”
Section: Estimation Of Annual Effective Dosementioning
confidence: 83%
See 2 more Smart Citations
“…About 72 samples of the most commonly used bottled waters of Bandar Abbas (Iran) which were collected for 3 consecutive months, May, June and July 2013 were studied [8]. 222 Rn concentration was measured with RTM1688-2 model.…”
Section: Introductionmentioning
confidence: 99%